The promise of mortgagein the Jordanian civil law - Albala’wi, Dr.Nasir (The journal of contemporary issues in business and government, 2021)
The researcher dealt with the subject of the promise of mortgage, and the most important conditions that must be met in order for us to be in front of a promise of mortgage that fulfill all the legal conditions in the first requirement of the research were discussed,then to talk about the most important implications of the promise of mortgage in the second requirement of this research. The problem of the research lies in clarifying the adequacy of the legal texts regulating the provisions of the mortgage, so that the legislator did not deal with the issue of the promise of the mortgage within these rules, and on the other hand, the statement of the extent to which the general rules related to the promise to contract on the promise of mortgage can be dropped. The researcher followed the descriptive analytical approach to answer the problem posed in the research by describing the problem under study and analyzing the legal texts regulating the subject using jurisprudence opinions and jurisprudence of the courts.